Gurcharan or Woodland Protected Forests in Thana (Bombay State) - Umbarje, S. R. (Indian Forester, 1952)
The paper deals with the protected forests in the Thana District of Bombay State which are under the dual control of the Revenue Department as well as the Forest Department. A short history of its management in the past is given. Causes for their deterioration are discussed and remedies are suggested.